Wolves, horses, bitches and other characters of gender violence in the work of Carolina Bianchi - Dalgalarrondo, Luisa (Revista Brasileira de Estudos da Presença, 2024)
This text analyzes the works of Carolina Bianchi, mainly LOBO (2018), O Tremor Magnífico (2020) and Trilogia Cadela Força – Capítulo I: A noiva e o Boa Noite Cinderela (2023). The article presents the artist, her most recent works and discusses how Bianchi brings into play the debate on gender violence, mainly through three thematic axes: the role of women in the History of Art, exploration of non-normative sexualities and the presence of non-humans in her works, which call for the debate about nature versus culture. It is dis-cussed how the artist articulates these elements on stage using strategies that seek to reveal tensions and contra-dictions, without presenting a resolution, but present an investigation of language and encourage critical and lively reflection.